Lutra lutra - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lutra lutra (Linnaeus, 1758). Syst. Nat., 10th ed., 1:45. TYPE LOCALITY: Sweden, Uppsala. DISTRIBUTION: Eurasia (excl. tundra and desert); British and Japanese Isis.; N. W. Africa; S. India; Sri Lanka; Taiwan; Vietnam; Sumatra; Java. PROTECTED STATUS: CITES - Appendix I. ISIS NUMBER: 5301412004024001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 258, DOI: 10.5281/zenodo.7352980